The APTIMA HPV assay versus the hybrid capture 2 test in triage of women with ASC-US or LSIL cervical cytology: a meta-analysis of the diagnostic accuracy - Arbyn, Marc; Roelens, Jolien; Cuschieri, Kate; Cuzick, Jack; Szarewski, Ann; Ratnam, Sam; Reuschenbach, Miriam; Belinson, Suzanne; Belinson, Jerome L.; Monsonego, Joseph (International journal of cancer, 2013)
Testing for DNA of 13 high-risk HPV types with the Hybrid Capture 2 (HC2) test has consistently been shown to perform better in triage of women with cervical cytology results showing atypical squamous cells of undetermined significance (ASC-US) but often not in triage of low-grade squamous intraepithelial lesions (LSIL) detected in cervical cancer screening. In a meta-analysis, we compared the accuracy of the APTIMA HPV test, which identifies RNA of 14 high-risk HPV types, to HC2 for the triage of women with ASC-US or LSIL. Literature search-targeted studies where the accuracy of APTIMA HPV and HC2 for detection of underlying CIN2/3+ was assessed concomitantly including verification of all cases of ASC-US and LSIL. HSROC (Hierarchical Summary ROC) curve regression was used to compute the pooled absolute and relative sensitivity and specificity. Eight studies, comprising 1,839 ASC-US and 1,887 LSIL cases, were retrieved. The pooled sensitivity and specificity of APTIMA to triage ASC-US to detect underlying CIN3 or worse was 96.2% (95% CI = 91.7-98.3%) and 54.9% (95% CI = 43.5-65.9%), respectively. APTIMA and HC2 showed similar pooled sensitivity; however, the specificity of the former was significantly higher (ratio: 1.19; 95% CI = 1.08-1.31 for CIN2+). The pooled sensitivity and specificity of APTIMA to triage LSIL were 96.7% (95% CI = 91.4-98.9%) and 38.7% (95% CI = 30.5-47.6%) for CIN3+. APTIMA was as sensitive as HC2 but more specific (ratio: 1.35; 95% CI = 1.11-1.66). Results were similar for detection of CIN2 or worse. In both triage of ASC-US and LSIL, APTIMA is as sensitive but more specific than HC2 for detecting cervical precancer.